Wildfire tendencies in Ukrainian forests - Voron, V. P.; Melnyk, Ye. Ye. (Forestry and Forest Melioration, 2019)
Introduction For the biosphere to function properly, it is absolutely necessary to preserve and increase forests area. Forest ecosystems in most regions of the world suffer from fires. According to recent data, there is a tense and difficult situation with forest fires in Ukraine, too. Therefore, it is an urgent issue which requires constant study and research. The aim of the study was to analyse the dynamics of forest fires in Ukraine, including the forests under the management of State Forest Resources Agency of Ukraine (SFRAU), and to identify the extent and depth of forests fires in various Ukrainian forestry and administrative areas. Materials and Methods We analysed the data on forest fires occurred both in Ukraine from 2000 to 2017 and in the forests under the management of the State Forest Resources Agency of Ukraine for the period 1992-2017. We calculated the average annual number of fires and their area, as well as the fire danger which took place in the forests in these territories for 2007–2017. The number and area of fires in different administrative and forest areas of State Forest Resources Agency of Ukraine in years 2015, 2016 and 2017 were determined. Then we compared the obtained data with natural factors and anthropogenic impact in different administrative and forestry areas. Results The number and area of fires from 2000 to 2017 in the State Forest Resources Agency’s forests varied from 806 to 5024 cases in some years, and the area of forest damaged by fire was 0.2–12.2 thousand ha. We found out that the maximum value for the number of fires exceeded the minimum one by 9.3 times, and that in area of fires by 75 times. At the same time, by number and cases the part of the fires in SFRAU forests ranged from 58 to 88%, and in the area of fires the difference was even larger, namely from 18 to 92%. It is worth noting that in the forests under State Forest Resources Agency’s jurisdiction, there is a significant amount of fires but the operational fire detection and extinguishing do not allow the fire to cover large areas. By defining spatial tendencies of fires in different forestry and administrative regions of Ukraine, we established that the number of fires and their area are significantly different, and they have their own specificities. Also, there is an extremely large difference in relative fire danger. A number of flame developments mainly depends on anomalously dry weather conditions. The fire area will depend on how fast it is detected and how effective fire extinguishing is carried out. We analyzed fire development in the forests of Kharkiv Region during the period from 1989 to 2015 and found out that almost 60% of fires occur in the forests of Kharkiv green zone. Conclusions The fires number and their area in Ukraine’s forests in some decades vary significantly. Thus, the largest numbers were detected in the 1990s, and the least ones in the 1980s and 2010s. For the period from 2000 to 2017, the number of fires in the SFRAU forests significantly varied. The maximum fire number exceeds the minimum one by 9.3 times, and the largest number of the area of fires exceeds the least one by 75 times. The part of fires in the SFRAU forests of the Agency varied from 58 to 88% in all forests of Ukraine. At the same time, the number of fires and fire danger in Ukrainian forestry area is significantly different. 1 Fig., 3 Tables, 27 Refs.